Assessment of the parasitic burden in the smallholder pig value chain and implications for public health in Uganda - Roesel, Kristina (2018)
The surging demand for pork in Uganda provides an opportunity to set poor farmers on pathways out of poverty by increasing production and market access. At the same time, markets have become more complex and threaten the continuous presence of smallholder farmers: pig diseases and other factors hinder a constant supply while foodborne diseases may impair the quality and safety of the farmers’ products. The intensification level may affect the parasitic burden of pigs and hence the profitability of pig farming as well as the risk to human health associated with pork borne parasites. Research on parasitic hazards in smallholder pig value chains in Uganda has so far been limited, and therefore, the present study aims, as described in chapter 1, to contribute to improving selected smallholder pig value chains in Uganda by increasing the evidence base on prevalent parasitic diseases. Chapter 2 outlines the history of pigs in Africa, describes the current smallholder pig production systems in sub-Saharan Africa, and reviews the current state of knowledge on parasitic pig diseases compromising farm productivity as well as parasitic diseases that are potentially transmitted to humans through pork consumption or for which pigs are known to be a natural disease reservoir. The review refers to previous research from sub-Saharan Africa, and particularly Uganda. Chapter 3 describes the context of the study and how it fits into overarching research for development on smallholder pig value chains in Uganda led by the International Livestock Research Institute (ILRI). It further describes how 35 villages were selected to be included into the survey, how value chain systems were defined as a proxy for the level of intensification, and characteristics of the area under study. Chapter 4 shows that both endo- and ectoparasites are perceived as an important production constraint by smallholder pig farmers in Central and Eastern Uganda, second only to African swine fever. Herd dynamics and husbandry practices in the predominating production settings were established by means of participatory rural appraisals with 340 smallholder pig farmers in the selected sites. Consecutively, a cross-sectional parasitological study in 21 of the 35 selected villages established baseline information on the rate and determinants of infection with gastrointestinal helminths and coccidia in 932 randomly sampled pigs between 3 to 36 months of age. The majority of pigs (61.4%; 95% confidence interval [CI]: 58.2-64.5%) tested positive for one or more gastrointestinal helminths, namely strongyles (57.1%; 95% CI: 53.8-60.3%), Metastrongylus spp. (7.6%; 95% CI: 6.1-9.6%), Ascaris suum (5.9%; 95% CI: 4.5-7.6%), Strongyloides ransomi (4.2%; 95% CI: 3.1-5.7%) and Trichuris suis (3.4%; 95% CI: 2.4-4.8%). Coccidia oocysts were found in 40.7% of all pigs sampled (95% CI: 37.5-44.0%). All animals tested negative for Fasciola spp. and Balantidium coli. There were no statistically significant differences in prevalence across value chain domains, and regression analysis showed that routine management factors had a greater impact on the prevalence of infection than regular preventive medical treatment or the level of confinement. Chapter 5 provides baseline information on two pork borne zoonoses of global importance, namely infection with Trichinella spp. and Toxoplasma gondii, in the same cohort of pigs. Trichinella-specific immunoglobulin G was found in 6.9% of the animals (95% CI: 5.6-8.6%) using a commercially available enzyme-linked immunosorbent assay (ELISA). Confirmatory testing by Western blot implied an overall seroprevalence of 2.1% (95% CI: 1.4-3.2%), and attempts to isolate muscle larvae using artificial digestion were unsuccessful. Implications for diagnostics were discussed and the risk to pork consumers for developing trichinellosis was classified as low. Antibodies to T. gondii were found in 28.7% of the animals (95% CI: 25.8-31.7%) at significantly higher levels in urban areas of production and consumption, and risk factors that potentially contribute to infection (e.g. biosecurity practices and access to cats) were identified. Chapter 6 outlines the findings on common preparation and consumption practices as well as sources of pork for consumption in the study area. These show that pork is very popular among pig farmers. In rural areas it is consumed mostly during seasonal festivities and whenever cash is available, in urban areas much more frequently. Pig feed production does not compete with human food production, and some festivals when pork is consumed even coincide with times when other food is scarce. The consumption of raw pork is considered unsafe, and at home meat is cooked for at least one hour. Chapter 7 discusses the findings, conclusions and limitations of the overall study and generates recommendations for potential interventions and further research. Parasitic infections in smallholder pig value chains in Uganda are common; and while no significant difference was observed in overall infection rates with gastrointestinal helminths, specific parasites were detected at significantly higher levels in urban (e.g. T. gondii) or rural value chain types (e.g. Trichinella spp.). Further in-depth research is needed to identify the circulating Trichinella spp. and T. gondii genotype, as well as more experimental and longitudinal studies to quantify economic losses of parasite infection, and to establish predominant transmission routes and thus control points for parasite control.